Hypothesis generative head-to-head study comparing efficacy of afatinib and osimertinib based on immunological biomarkers in Japanese NSCLC patients with EGFR mutations (Heat on Beat study). (October 2020) - Morikawa, Kei; Tanaka, Hisashi; Itani, Hidetoshi; Takata, Saori; Watanabe, Satoshi; Kishi, Kazuma; Soejima, Kenzo; Kaira, Kyoichi; Kagamu, Hiroshi; Yoshimura, Kenichi; Matsutani, Noriyuki; Seki, Nobuhiko
Background: In the FLAURA trial, superiority of osimertinib over the standard of care (SOC) was not demonstrated in Asian patients; SOC seemed favorable among Japanese patients (hazard ratio 1.39, 95% confidence interval 0.82–2.33). Three reasons are suggested: since rechallenge with epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) is covered by health insurance in Japan, EGFR-TKI rechallenge rate was higher in SOC than in the osimertinib group, which resulted in a long-term sequential administration of EGFR-TKIs; treatment discontinuation rate was high in the osimertinib group due to adverse events such as interstitial pneumonia among Japanese patients. EGFR-TKIs enhance tumor antigen-specific cytotoxicity of T cells, especially first- and second-generation EGFR-TKIs, which are more active against various cells with wild-type EGFR, including regulatory T cells. Consequently, subsequent immune checkpoint inhibitor therapy seemed more promising in the SOC group. Therefore, optimal first-line EGFR-TKI for EGFR-mutant advanced lung cancer may not have been identified in Japanese patients. Methods: The Heat on Beat study is a randomized, open-label, multicenter, phase II study to compare OS between initial treatment with afatinib and osimertinib in treatment-naïve patients with advanced or recurrent EGFR-mutant NSCLC. Exploration of immunomonitoring through peripheral blood mononuclear cells will also be performed, before, during, and after treatment. Treatment-naïve EGFR mutation-positive non-small cell lung cancer (NSCLC) patients ( N = 100) will be randomized to two groups in a 1:1 ratio. The co-primary endpoints are 3-year survival rate and characterization of immune environment associated with response to afatinib, osimertinib, or immune checkpoint inhibitors. Enrollment will start in May 2020 at 28 sites in Japan and continue for 1 year, with 3-year follow-up. Discussion: Because there is no clinical trial comparing second- with third-generation EGFR-TKI for advanced EGFR-mutant NSCLC, our study would provide a major impact on clinical practice. Trial registration Japan Registry of Clinical Trials, jRCTs031190221, registered date: 25 February 2020, https://jrct.niph.go.jp/en-latest-detail/jRCTs031190221